Egyptian pediatric guidelines for the management of childhood venous thromboembolism: the adapted methodology: a limited resource country perspective - Galila Mokhtar; Ashraf Abdelbaky; Amira Adly; Dina Ezzat; Hanafy Hafez; Hoda Hassab; Ilham Youssry; Iman Ragab; Laila M. Sherief; Marwa Zakaria; Mervat Hesham; Mervat Mansour; et al. (Thrombosis Journal)
Abstract Background Thrombosis is a major pediatric health problem with a spectrum of etiologies, clinical presentations, and morbidities. Establishing the diagnosis and treatment of pediatric thrombosis with different site-related presentations may be challenging. This article adapts the high-quality Clinical Practice Guidelines (CPGs) for pediatric thrombosis management to suit the Egyptian healthcare context. Methods The adapted ADAPTE methodology was used to identify the high-quality CPGs published between 2012 and 2023. An expert panel screened, reviewed, and assessed the CPGs and formulated the adapted consensus recommendations based on the best available evidence. Results The final CPG document provides consensus recommendations and implementation tools for managing thrombosis with different etiologies in children and adolescents in Egypt. There is no evidence to support strong recommendations for various management approaches. Conclusions In general, a complete clinical and radiological assessment and some laboratory tests are indicated at the initial diagnosis to confirm a thrombotic disorder and to further choose the type of workup required. Future research should report the outcome of this adapted guideline and include cost-analysis evaluations.